Residencia multifamiliar - Leiva Montoya, Santiago Fernando (2020)
El Batán is a neighborhood located on slopes with winding streets and staggered buildings which have problems in the mobility and legibility of the sector. Due to the aforementioned, and urban plan has been developed that seeks to solve the previously raised inconveniences. The main concepts used for the understanding and investigation of the neighborhood are: diversity, porosity, permeability and legibility through which different socio-cultural and environmental dynamics are promoted that foster the creation of safe public spaces in which there is social cohesion. The proposed conceptual proposal divides the sector into sub zones called clusters, within which is the Río Coca cluster, whose proposal is to articulate various nodes that becomes squares and parks that will complement public spaces, thus seeking to increase the sense of identity and belonging in the users. Within this cluster, different facilities were proposed, including the planning of a Multi-Family Residence that will be located between the following routes: Ave. Río Coca, Street De los Colimes, Street Isla Marchena and Street Joel Polanco, in order to supply the population projected towards the year 2040 whose justification lies in a population analysis of the users, their family compositions and needs. The project will additionally have a permeable public space that gives residents the feeling of security, thus promoting the establishment of floating and permanent users within it.